If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + (-2) * x + -3 = 0 Reorder the terms: -4 + -3 + -2x = 0 Combine like terms: -4 + -3 = -7 -7 + -2x = 0 Solving -7 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -2x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -2x = 0 + 7 -2x = 0 + 7 Combine like terms: 0 + 7 = 7 -2x = 7 Divide each side by '-2'. x = -3.5 Simplifying x = -3.5
| 14m-32=22 | | 15x^2-165x+630=0 | | x+2+x+2+x+2=36 | | X^2=1966 | | -16x^2+150x-3=0 | | 5x^2-12=-8x | | 8(x+7)+6=8.6x-6 | | 5w^2-60=0 | | 7.3x+1.8=1.5+4(x-6.6) | | 9x^2-140x+528=0 | | 9x-2=9(x-3) | | 0=112t-16t^2 | | 16x^2-35x+80=0 | | 2=55t-5t^2 | | 4.1x+7=-2+9.6(x-9) | | x=3xd-21 | | 3absx-4=10 | | 5x-2(-3x-8)=-98 | | -4y+12=-2(4y-6) | | 4xp+6= | | -2x-1-4x=2x+2-5x-15 | | 9.3(x+6)+4=8 | | -8-13=6x+17-5x | | 5(x+8)+57=-2x | | -4y+4=2(3y+2) | | 2x+3x+2x+3= | | y+3.2=-6.4-4.5 | | 3(x-9+4x-1)-2(9-x)=-65 | | x-21=25 | | 5(x+3)=90 | | 2y-30+x=180 | | -4(y+9)=-3y-2 |